Long-term stability and zero drift of digital barometric pressure gauges. (11th March 2015) - Kojima, M; Kobata, T; Fujii, K
Abstract: Several digital pressure gauges at the National Metrology Institute of Japan (NMIJ) have been calibrated in the barometric pressure range on a regular basis for over ten years. The long-term stability of the zero and span readings for these pressure gauges was evaluated using their historical calibration data. The evaluation showed that most of the gauges have quite good long-term stabilities for the span readings, but some have large zero drifts with rates of about (10 to 50) Pa yr −1 . This paper discusses the causes for this drift: it can be explained by the combination of a small leak and gas emissions from the sensor volume, which are estimated from the typical drift rates. The zero drift of a particular gauge is well-approximated by an exponential function of time; the fitting function may give a good estimation of the zero drift in the future. This indicates that continuous characterization of a pressure gauge may enable appropriate correction of the indication and provide users more reliable data with less calibration work.